Larval morphology of the Western Balkans endemic caddisflies Drusus krusniki Malicky 1981, D. vernonensis Malicky 1989, and D. vespertinus Marinković-Gospodnetić 1976 (Trichoptera, Limnephilidae, Drusinae) - Waringer, Johann; Previšić, Ana; Kućinić, Mladen; Graf, Wolfram; Vitecek, Simon; Keresztes, Lujza; Bálint, Miklós; Pauls, Steffen U. (Zootaxa, 2016)
Drusinae (Trichoptera, Limnephilidae) are highland caddisflies inhabiting high-gradient, turbulent running water and spring habitats. They are disjunctly distributed over the Eurasian mountain ranges, and the majority of species are endemic to particular mountain areas. The most diverse of three main groups of the Drusinae, the grazer clade, consists of species in which larvae feed on epilithic biofilm and algae. In this paper we describe three previously unknown grazer-clade Drusinae larvae: Drusus krusniki Malicky 1981 (endemic to the Dinaric Western Balkans), D. vernonensis Malicky 1989 (endemic to the Hellenic Western Balkans), and D. vespertinus Marinković-Gospodnetić 1976 (endemic to the Dinaric Western Balkans). The larvae of these species have toothless mandibles typical of the Drusinae grazer clade. Larvae and adults were unambiguously associated using molecular genetic data, i.e., the mitochondrial cytochrome oxidase I gene fragment (mtCOI3-P). Morphological characteristics of the larvae are described and the diagnostic features enabling species-level identification are illustrated. We further discuss the ecology and distribution of the three Western Balkan endemic species.